Introducing Effective Techniques of Study in English Language - Begzada, Sultana (Integrated Journal for Research in Arts and Humanities, 2024)
The study has a valuable role in learning of different languages especially in English language. The effect of study in language can be detected when it comes with certain and useful methods and techniques. As the major methods that affect English include of time management, note taking, setting goals, preparing for exam, making plan, reading strategies and the techniques of study of the subjects. This research shows that the introducing effective techniques of study in English language. The research of analytical and descriptive library method was used in the preparation and research of this article.